FROM SILENCE TO VIRAL: DIGITAL PUBLIC SPHERE AND COMMUNITY RESISTANCE ON SOCIAL MEDIA - Sari, Jelita Purnamasari; Rahmah Agustiani; Hepi Hastuti; Ismail Ibrahim (Gema Kampus IISIP YAPIS Biak, 2026)
This study examines how indigenous communities in Biak Numfor, Papua, Indonesia utilize Facebook as a digital public sphere to construct resistance narratives against land acquisition for military and infrastructure projects. Through qualitative content analysis and critical discourse analysis of 15 viral Facebook posts from December 2025 to February 2026, this research investigates the narrative strategies, framing techniques, and symbolic mobilization employed by the #BiakBukanTanahKosong movement. Findings reveal three dominant narrative frames: indigenous sovereignty and ancestral rights, generational justice and future identity, and institutional betrayal and elite complicity. The study identifies key virality mechanisms including hashtag activism, emotional storytelling, networked solidarity, and strategic use of local language alongside Indonesian. The analysis demonstrates that viral digital resistance generates significant discursive power but faces limitations in translating online momentum into concrete policy reversal without sustained offline mobilization. This research contributes to understanding how peripheral communities leverage social media to bypass traditional gatekeeping and exert policy pressure in Indonesia's constrained civic space.